Parents' work patterns and adolescent health and wellbeing - Dockery, Alfred Michael; Li, Jianghong; Kendall, Garth (ELSEVIER, 2009)
Previous research demonstrates that non-standard work schedules undermine the stability of marriage and reduce family cohesiveness. Limited research has investigated the effects of parents working non-standard schedules on children's health and wellbeing and no published Australian studies have addressed this important issue. This paper contributes to bridging this knowledge gap by focusing on adolescents aged 15-20 years and by including sole parent families which have been omitted in previous research, using panel data from the Household, Income and Labour Dynamics in Australia Survey. Multilevel linear regression models are estimated to analyse the association between parental work schedules and hours of work and measures of adolescents' mental health derived from the SF-36 Health Survey. Evidence of negative impacts of parents working non-standard hours upon adolescent wellbeing is found to exist primarily within sole parent families.